Aggressive tumor microenvironment of solid predominant lung adenocarcinoma subtype harboring with epidermal growth factor receptor mutations. (January 2016) - Saruwatari, Koichi; Ikemura, Shinnosuke; Sekihara, Keigo; Kuwata, Takeshi; Fujii, Satoshi; Umemura, Shigeki; Kirita, Keisuke; Matsumoto, Shingo; Yoh, Kiyotaka; Niho, Seiji; Ohmatsu, Hironobu; Ochiai, Atsushi; et al.
Highlights: We retrospectively analyzed 214 patients with EGFR mutant adenocarcinoma. SPA displayed worse prognosis than the other subtypes. Cancer cells of SPA showed higher expression of ezrin, laminin-5, and PD-L1. Stromal cells of SPA displayed higher levels of PDPN-CAFs, CD204-TAMs and CD34-MVs. Cancer cells and stromal cells of SPA create more aggressive tumor microenvironment. Abstract: Introduction: Tumor microenvironment critically affects cancer progression. This study aimed to identify differences in microenvironments of lung adenocarcinomas with epidermal growth factor receptor (EGFR) mutations by histological subtypes. Methods: The study cohort included 214 lung adenocarcinomas harboring EGFR mutations. We analyzed clinicopathological characteristics of lepidic (LPA), papillary (PPA), acinar (APA), and solid-predominant adenocarcinoma (SPA) subtypes, and examined expression levels of EGFR, E-cadherin, ezrin, laminin-5, ALDH1, and PD-L1 in cancer cells, and of CD34, CD204, podoplanin (PDPN), and FoxP3 in stromal cells in 4 subtypes ( n  = 20 each). Results: SPA displayed significantly more frequent lymph node metastasis, lymphovascular invasion, and worse prognosis than the other subtypes. Ezrin expression levels in SPA were also significantly higher than in LPA, PPA, or APA ( P  < 0.05, all). Laminin-5 and PD-L1 expression levels in SPA were significantly higher than in LPA ( P  < 0.01 for both) and PPA ( P  < 0.01 for both) and tended to be higher than in APA (laminin-5: P  = 0.096, PD-L1: P  = 0.081). Furthermore, SPA displayed higher levels of PDPN (+) cancer-associated fibroblasts ( P  < 0.01) and CD204 (+) tumor-associated macrophages ( P  < 0.05) than the other subtypes. Conclusion: Compared with other predominant subtypes with EGFR mutations, the microenvironment of SPA with EGFR mutations is characterized by cancer cells with higher invasive and immune evasion potential and more abundant stromal cells with tumor-promoting functions, which would contribute to the more aggressive behavior of SPA.